2015
DOI: 10.1002/mbo3.262
|View full text |Cite
|
Sign up to set email alerts
|

UV ‐resistant yeasts isolated from a high‐altitude volcanic area on the Atacama Desert as eukaryotic models for astrobiology

Abstract: The Sairecabur volcano (5971 m), in the Atacama Desert, is a high-altitude extreme environment with high daily temperature variations, acidic soils, intense UV radiation, and low availability of water. Four different species of yeasts were isolated from this region using oligotrophic media, identified and characterized for their tolerance to extreme conditions. rRNA sequencing revealed high identity (>98%) to Cryptococcus friedmannii, Exophiala sp., Holtermanniella watticus, and Rhodosporidium toruloides. To o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 86 publications
6
45
0
2
Order By: Relevance
“…Also relevant to the present study, Vimercati et al (2016) showed that the isolate from Volcán Llullaillaco (discussed below) forms a monophyletic clade with N. friedmannii based on long-read 18S environmental sequences (1739 bp, JX099190) from Llullaillaco (Lynch et al 2012). Likewise, the Naganishia isolate from Volcán Saírecabur studied by Pulschen et al (2015) showed 100% identity with N. friedmannii over a 599 bp region of the LSU rRNA gene.…”
Section: Phylogeny Of the Naganishia Cladementioning
confidence: 94%
See 4 more Smart Citations
“…Also relevant to the present study, Vimercati et al (2016) showed that the isolate from Volcán Llullaillaco (discussed below) forms a monophyletic clade with N. friedmannii based on long-read 18S environmental sequences (1739 bp, JX099190) from Llullaillaco (Lynch et al 2012). Likewise, the Naganishia isolate from Volcán Saírecabur studied by Pulschen et al (2015) showed 100% identity with N. friedmannii over a 599 bp region of the LSU rRNA gene.…”
Section: Phylogeny Of the Naganishia Cladementioning
confidence: 94%
“…are 25–33% higher than levels measured at lower elevation sites in the Atacama (Yungay, 948 m.a.s.l. ; Pulschen et al 2015). Also of relevance to this paper is the fact that the tephra soils on these high volcanoes are among the most oligotrophic soils or sediments yet studied.…”
Section: The Environmental and Biogeochemical Settingmentioning
confidence: 98%
See 3 more Smart Citations